PENGARUH PENDELEGASIAN WEWENANG TERHADAP KINERJA ORGANISASI - Galih Fajar Muttaqin (Jurnal Riset Akuntansi Terpadu, 2018)
The purpose of this study is to determine the Effect of Delegation of Authority on Or- ganizational Performance with Change of Management Accounting System as Intervening Vari- able. This research was conducted at the Manufacturing Company located in Serang District. As the object of his research, the middle manager with 125 questionnaires spread, but the question- naire that can be processed as much as 72 questionnaires (58%). The questions questionnaire measured with a scale of 1-5. Data were analyzed by using SEM (Structural Equation Model) through SmartPLS (Partial Least Square) 2.0 versions. The results of this study indicate (1) Delegation of authority has a positive effect on Management Accounting System Changes, (2) Changes in Management Accounting System has a positive effect on Organizational Performance, and (3) Delegation of Authority positively af- fects organizational performance.